THE INFLUENCE OF ISLAMIC BOARDING SCHOOL CULTURE ON THE CHARACTER BUILDING OF SANTRI - Virgin Sabrina El-Islamy; Firda Al Husnia; Nurul Yaqien (Universitas Nurul Jadid, 2023)
This study focuses on the influence of pesantren culture on the formation of student character at Queen Al-Falah Ploso Kediri Islamic Boarding School. The purpose of this study was to determine the influence of pesantren culture on the formation of student character at Queen Al-Falah Ploso Kediri Islamic Boarding School. This study used a quantitative approach, where researchers collected data using questionnaires, interviews and documentation techniques. The method used in this study is an inferential analysis method with multiple linear regression analysis. Sampling of 40 students. The results of this study show that the influence of pesantren culture on the formation of student character at Queen Al-Falah Ploso Kediri Islamic Boarding School has a strong and significant influence of 27.3%, meaning that pesantren culture is significantly related to the formation of student character. While 72.7% is determined by other factors.The implications of these findings show the need for a deeper understanding of external factors that also influence the formation of student character in pesantren.